A Novel Method of Twist Drill Fluting Fulfilling Required Web Thickness and Rake Angle - Zhuyu, Li; Hongyang, Wang; Jianzhong, Hu; Wei, Zhang (IOP conference series. Materials Science and Engineering, 2018)
As substitute of the meshing theory based fluting method, other analytical, machining movement simulation or empirical method are developed in last decades. Currently, a kind of flute prevails. It is ground by using 1V1/1A1 standard grinding wheel and should fulfil requirements of designated web thickness and radial rake angle. This paper presents a novel method by straightforwardly determining install position of the grinding wheel. Based on the relative movement with variables' parameterization, equations to keep web thickness are firstly derived. Then, a family of flute cross-sectional curves is computed automatically with respect to grinding process parameters and wheel geometry. The calculation process is characterized by concise in principle and easy to use. Its validity is verified by good agreement between the results computed and manufactured example.